Correction: The Association of Exposure to Urban Greenspace and Depression in Women. - Taheri, Esmat; Faramarziniya, Arian; Khosrorad, Razieh; Najafi, Moslem Lari; Joveini, Hamid; Khamirchi, Mohammad; Heydari, Hafez; Kaffash, Leila Haghighi; Ghorbani, Alireza; Niko, Fatemeh; Shobeyri, Faeze Sadat; Aval, Mohsen Yazdani; et al. (Journal of Urban Health, 2025)
The article focuses on the correction of a previously published work regarding the authorship of a study in the field of urban health. It specifically addresses the misspelling of coauthor Hamid Joveini's name and confirms that the original article has been amended. The publisher, Springer Nature, emphasizes its neutrality concerning jurisdictional claims in published maps and institutional affiliations. This correction is part of maintaining accuracy and integrity in academic publishing.